Application of a novel phage vB_SalS-LPSTLL for the biological control of Salmonella in foods. (September 2021) - Guo, Yating; Li, Jie; Islam, Md. Sharifull; Yan, Ting; Zhou, Yang; Liang, Lu; Connerton, Ian F.; Deng, Kai; Li, Jinquan
Graphical abstract: Highlights: We isolated a novel phage LPSTLL with broadest lytic range infecting Salmonella among the reported phages. A new genus of Siphoviridae family, LPSTLLvirus, with LPSTLL as the type phage, was proposed. LPSTLL has ability as a candidate for Salmonella biocontrol agent in the food matrices without impact on the sensory quality. Abstract: Salmonella is one of the most common foodborne pathogens around the world. Phages are envisioned as a new strategy to control foodborne pathogenic bacteria and food safety. A Salmonella specific lytic phage vB_SalS-LPSTLL (LPSTLL) was selected for food applications on the basis of lytic range, lytic efficiency, functional stability and characteristics. Phage LPSTLL was able to lyse 11 Salmonella serotypes, which represents the broadest range reported Salmonella phages, and was able to suppress the growth of Salmonella enterica in liquid culture over nine hours. LPSTLL exhibited rapid reproductive activity with a short latent period and a large burst size in one-step growth experiment. LPSTLL remained active over a pH range of 3.0 to 12.0, and at incubation temperatures up to 60 °C for 60 min, indicating wide applicability for food processing and storage. Significant reductions of viable Salmonella were observed in diverse foods (milk, apple juice, chicken and lettuce) with reductions up to 2.8 log CFU/mL recorded for milk. Sensory evaluation indicated that treatment with phage LPSTLL did not alter the visual or tactile quality of food matrices. Genome analysis of LPSTLL indicated the absence of any virulence or antimicrobial resistance genes. Genomic comparisons suggest phage LPSTLL constitutes a novel member of a new genus, the LPSTLLvirus with the potential for Salmonella biocontrol in the food industry.